PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PANTI GRIA JANNATI PROVINSI GORONTALO - Hamna Vonny Lasanuddin (Pusat Riset dan Inovasi Nasional, 2021)
Hand washing is carried out before and after carrying out nursing actions even though wearing gloves and other personal protective equipment. This action is to reduce the microorganisms on the hands so that the spread of infection can be reduced. when washing hands, is when hands are dirty, when arriving and before leaving the hospital, before and after performing the procedure, contact with patients, the patient's environment, before and after preparing food, and after going to the bathroom. Hand washing indicators are used and must be done to anticipate the transfer of germs through the hands. hand sanitizer that functions as an antiseptic, hand lotion, and under yellow plastic for contaminated or infected waste), dryers such as tissues, hand towels, gloves (gloves), liquid soap or liquid wastefel there are footwear from towel